Stilistika Al-Qur'an: Suatu Analisis Linguistik: The Stylistics of the Qur'an: A Linguistic Analysis - Siregar, Juwairiyah; Agustiar (An-Nahdah Al-'Arabiyah is published by Department of Arabic Language and Literature in cooperation with The Center for Research and Community Service (LP2M), 2024)
The Qur'an, as a holy book, has an extraordinary beauty of language style. Research on the style of the Qur'an is increasingly widespread, and new theories continue to emerge to analyze it more deeply. One example is stylistics. This study aims to understand in depth the meaning of Qur'anic stylistics, its function and purpose, and the scope of stylistic studies. This research was conducted by reviewing literature and library sources in the form of scientific articles and books. This study found that Qur'anic stylistics is a science that studies language style, where the language style itself is a distinctive or unique way that exists in the Qur'an to convey something effectively and achieve certain goals. The function of stylistics is a tool to unlock meaning in literary works and the Qur'an. The aim of this field is to reveal and explain the meaning behind the use of beautiful language in a text. The scope of the study of stylistics includes various linguistic elements, namely phonology, morphology, syntax and semantics, to understand the meaning and style of language contained in a text. This research enriches the understanding of the concept or theory of Qur'anic stylistics, its function, and the scope of its study and can be applied to analyze stylistics in the Qur'an. القرآن الكريم، باعتباره كتاباً مقدساً، يتميز بجمال لغوي استثنائي. الأبحاث حول أسلوب القرآن تزداد انتشاراً، وتستمر النظريات الجديدة في الظهور لتحليله بشكل أعمق. أحد هذه النظريات هو علم الأسلوب. تهدف هذه الدراسة إلى فهم معنى علم الأسلوب القرآني، وظيفته وهدفه، ونطاق الدراسات الأسلوبية بشكل معمق. تم إجراء هذا البحث من خلال مراجعة الأدبيات والمصادر المكتبية على شكل مقالات علمية وكتب. وجدت هذه الدراسة أن علم الأسلوب القرآني هو مجال دراسي يدرس أسلوب اللغة، حيث أن أسلوب اللغة نفسه هو طريقة مميزة أو فريدة توجد في القرآن لنقل شيء ما بفعالية وتحقيق أهداف محددة. وظيفة علم الأسلوب هي أن يكون أداة لفك شفرة المعنى في الأعمال الأدبية والقرآن. الهدف من هذا المجال هو كشف وشرح المعنى وراء استخدام اللغة الجميلة في النص. يشمل نطاق الدراسات الأسلوبية مختلف العناصر اللغوية، وهي علم الأصوات، وعلم الصرف، والنحو، والدلالات، لفهم معنى وأسلوب اللغة الموجودة في النص. هذا البحث يغني فهم مفهوم أو نظرية علم الأسلوب القرآني، وظيفته، ونطاق دراسته، ويمكن تطبيقه لتحليل الأسلوب في القرآن. Al-Qur'an, sebagai kitab suci, memiliki keindahan gaya bahasa yang luar biasa. Penelitian gaya bahasa Al-Quran semakin marak, dan teori-teori baru terus bermunculan untuk menganalisisnya secara lebih mendalam. Salah satu contohnya adalah stilistika. Penelitian ini bertujuan untuk memahami secara mendalam tentang pengertian stilistika Al-Qur’an, fungsi dan tujuannya, serta ruang lingkup kajian stilistika. Penelitian ini dilakukan dengan mengkaji literatur dan sumber pustaka berupa arikel ilmiah dan buku. Penelitian ini menemukan bahwa stilistika Al-Qur’an adalah ilmu yang mengkaji gaya bahasa, dimana gaya bahasa itu sendiri merupakan cara khas atau keunikan yang ada dalam Al-Qur’an untuk menyampaikan sesuatu secara efektif dan mencapai tujuan tertentu. Fungsi stilistika adalah alat untuk membuka makna dalam karya sastra dan Al-Qur'an. Tujuan ilmu ini adalah mengungkap dan menjelaskan makna di balik penggunaan bahasa yang indah dalam sebuah teks. Ruang lingkup kajian stilistika mencakup berbagai elemen linguistik, yaitu fonologi, morfologi, sintaksis, dan semantik untuk memahami makna dan gaya bahasa yang terkandung dalam sebuah teks. Penelitian ini memperkaya pemahaman tentang konsep atau teori tentang stilistika Al-Qur'an, fungsinya, dan ruang lingkup kajiannya serta dapat dilakukan penerapan teori untuk menganalisis stilistika dalam Al-Qur’an.